A New Approach for Lateral Sinus Floor Elevation. Issue 8 (November 2020) - Covani, Ugo; Giammarinaro, Enrica; Marconcini, Simone
Abstract : Abstract: The lateral sinus lift procedure has been extensively investigated and described as a reliable surgical solution aimed at facilitating implant placement and rehabilitation when the posterior upper maxilla is atrophic. The standard technique consists in a lateral antrostomy, the careful raising of the sinus membrane, and following apposition of a bone substitute between the membrane and the sinus floor. The present technical note illustrates a new conservative technique enabling lateral sinus lift without the use of bone substitutes and with predictable outcomes.